2015
DOI: 10.1007/s00170-015-7475-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical machining flow field simulation and experimental verification for irregular vortex paths of a closed integer impeller

Abstract: Electrochemical machining (ECM) is an economical and effective method for machining hard-to-cut metal materials into complex shapes in aerospace and aeronautics fields, which are difficult to machine with conventional methods. As we all know, electrolyte flow field is one of the important factors in ECM irregular vortex paths of the closed integer impeller. To improve the stability of the whole processing, the flow field mathematical model was developed. The 3-D gap flow field simulation models of the reversed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 34 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Tang et al compared the influence of different flow modes on ECM of a closed integer impeller. The results showed that the reverse flow mode achieved a higher electrolyte velocity and better machining results than the forward flow mode [18].…”
Section: Introductionmentioning
confidence: 97%
“…Tang et al compared the influence of different flow modes on ECM of a closed integer impeller. The results showed that the reverse flow mode achieved a higher electrolyte velocity and better machining results than the forward flow mode [18].…”
Section: Introductionmentioning
confidence: 97%
“…Li et al [8] simulated and tested the flow field of spin-printed electrolytic processing tabs, and the simulation analysis results showed that the flow field of spin-printed electrolytic processing was changing periodically; Liu et al [9] proposed a three-dimensional composite electrolyte flow field model for the electrolytic processing of engine blade discs, which improved the flow field state in the flow channel mutation region and effectively suppressed the flow field defects in the two -dimensional flow field;. Liu et al [10]used the "bi-directional feed" electrolyte flow mode for engine blade machining, which improved the machining quality of the blade; Tang et al [11] improved the stability of the electrolytic machining process by performing flow field analysis on the 3D gap flow field simulation model with reverse flow and forward flow. Liu et al [12] established A mathematical model of multi-physical field coupling in the process of reaming electrolytic processing in small holes,simulated using COMSOL Multiphisics software to obtain the flow rate distribution, current density distribution and temperature distribution in the processing gap, and the effects of different processing times and voltages on the temperature distribution were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the study of flow field mode, in 2013, Xu et al used Π shape flow mode to ECM the integrated blade cascade channel, and a more uniform flow field improved the processing quality, stability and efficiency [19]. Two years later, the reverse flow field was used to ECM for the closed integral impeller, showing that the whole process was stable, and the machining quality was high [20]. In 2020, Wang et al designed a new tangential flow field, which effectively eliminated the defect of sudden change of flow channel in ECM for large size blade [21].…”
Section: Introductionmentioning
confidence: 99%